Counterrealism and Indo-Anglian Fiction. - Kanaganayakam, Chelva (Wilfrid Laurier University Press, 2006)
What do R.K. Narayan, G.V. Desani, Anita Desai, Zulfikar Ghose, Suniti Namjoshi, and Salman Rushdie have in common? They represent Indian writing in English over five decades. Vilified by many cultural nationalists for not writing in native languages, they nonetheless present a critique of the historical and cultural conditions that promoted and sustained writing in English. They also have in common a counterrealist aesthetic that asks its own social, political, and textual questions. This book is about the need to look at the tradition of Indian writing in English from the perspective of.